Towards the Geopolitical-Economics of Conflict Over Resources: The Gate Valve Theory - Gabriel, Percival (Energy Economics Letters, 2017)
The aim of this paper is to present a theory that could give an account of the intersection between geography, politics and economics regarding resources. This theory assumes that “it is not only the actual source space or arterial space but also the informational constructs pertaining to the source space or arterial space that generate the gate valve effect on the global or secondary market of resources and their derivative products.” The gate valve effect is the dynamics of power exercised over the resource flow in the gate valve mechanisms whether spatial or informational. It is the resulting mechanism of control over resource flow. The geographic side of the theory pertains to the source location and arterial space defined by chokepoints where the resource passes or gets distributed. The economic side of the theory pertains to the informationally sensitive futures market of the resources. And the political side of the theory relates to the power-dynamics to control the source or arterial space or influence the market of the resource.